ANALISIS TDS, pH, BOD DAN COD UNTUK MENGETAHUI KUALITAS AIR SUMUR DAERAH KILOMETER 12 KOTA SORONG - Patawang, Sabdi; Kaikatui, Alexandro F.P; Lawalata, Raldo; Salossa, Melton; Ambarak, Anugerah S; Tombi, Yehezkiel; Kareth, Azer; Gombo, Tia; Jeuyanan, Efrena O. B; Luon, Emanuel R. M; Van Harling, Vina N (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to determine the quality of well water in the Kilometer 12 area of Sorong City and its impact on the surrounding community. The physical and chemical parameters tested include temperature, pH, TDS, COD, and BOD. Testing was carried out using a thermometer, pH meter, TDS meter, and COD Reactor at the PT. Pertamina International Refinery RU VII Kasim Laboratory. The analysis results showed that all parameters were in the good category: temperature 24°C, pH 6.5, TDS 172 ppm, COD 8 mg/L, and BOD 1 mg/L. These conditions indicate that the well water is not significantly contaminated and is suitable for domestic use. However, microbiological and heavy metal testing are still recommended to ensure consumption safety